EXPLORATION OF WILD EDIBLES FOR FOOD SECURITY, CURRENT KNOWLEDGE, AND FUTURE PROSPECTS (International Journal of Food and Nutritional Sciences, 2024)
The rapid increase in population and malnutrition is a major challenge for humanity. Factors suchas climate change, desertification, loss of biodiversity and rise in water scarcity have adverselyaffected food security. Wild edibles can play a significant role in food security by contributing todietary and agricultural biodiversity diversification. Wild edible plants are a potential source ofnutraceuticals. These plant species are alternative sources of food and nutrition and possessmedicinal properties. The current review focuses on exploring wild edibles for food security.